2000
DOI: 10.1097/00004647-200005000-00002
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative Assessment of Ischemic Pathology in Axons, Oligodendrocytes, and Neurons: Attenuation of Damage after Transient Ischemia

Abstract: Axons and oligodendrocytes are vulnerable to cerebral ischemia. The absence of quantitative methods for assessment of white matter pathology in ischemia has precluded in vivo evaluation of therapeutic interventions directed at axons and oligodendrocytes. The authors demonstrate here that the quantitative extent of white matter pathology was reduced by restoration of cerebral blood flow after 2 hours of middle cerebral artery occlusion. Focal ischemia was induced in anesthetized rats by intraluminal thread plac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
45
0

Year Published

2001
2001
2016
2016

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 59 publications
(53 citation statements)
references
References 32 publications
8
45
0
Order By: Relevance
“…21 However, more recently, methods for quantification of white matter damage have been developed. 16,17,22,28 With the use of APP accumulation to highlight axonal damage and Tau-1 staining for oligodendrocyte pathology, Valeriani et al 18 demonstrated that reperfusion of ischemic tissue salvaged axons and oligodendrocytes, in addition to neuronal perikarya from ischemic damage; Irving et al 22 demonstrated that a free radical scavenger but not an NMDA or AMPA antagonist could salvage oligodendrocytes; and Yam et al 17 reported the failure of the NMDA receptor antagonist MK-801 to influence axonal damage while producing a 30% reduction in gray matter damage compared with control. NMDA antagonists are targeted toward salvaging gray matter, the failure to protect against axonal damage most probably reflecting the lack of NMDA receptors in white matter.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…21 However, more recently, methods for quantification of white matter damage have been developed. 16,17,22,28 With the use of APP accumulation to highlight axonal damage and Tau-1 staining for oligodendrocyte pathology, Valeriani et al 18 demonstrated that reperfusion of ischemic tissue salvaged axons and oligodendrocytes, in addition to neuronal perikarya from ischemic damage; Irving et al 22 demonstrated that a free radical scavenger but not an NMDA or AMPA antagonist could salvage oligodendrocytes; and Yam et al 17 reported the failure of the NMDA receptor antagonist MK-801 to influence axonal damage while producing a 30% reduction in gray matter damage compared with control. NMDA antagonists are targeted toward salvaging gray matter, the failure to protect against axonal damage most probably reflecting the lack of NMDA receptors in white matter.…”
Section: Discussionmentioning
confidence: 99%
“…Failure to ameliorate ischemic damage to white matter has been proposed to be one of the major factors, 14 and the importance of white matter damage as well as gray matter in experimental stroke is increasingly recognized. [15][16][17][18] The first aim of this study was to comprehensively assess the neuroprotective efficacy of delayed treatment with an improved, intravenous formulation of ebselen in an established model of experimental stroke. We used conventional histopathology to assess gray matter damage (perikarya), quantification of subcortical white matter damage (axons and oligodendrocytes), and scoring of neurological deficit.…”
mentioning
confidence: 99%
“…Immunohistochemical detection of APP (Alzheimer precursor protein) was conducted according to Valeriani and colleagues (11). Dewaxed sections were microwaved for 10 min in 10 mmol/l citric acid (pH 6.0), allowed to cool, and incubated in 3% H 2 O 2 in methanol for 30 min and then for 1 h in 50 mmol/l PBS (pH 7.2) containing 0.5% bovine serum albumin and 10% normal horse serum.…”
Section: Methodsmentioning
confidence: 99%
“…This method has the advantage that it can be combined with quantitative histology to determine neuronal damage, and with immunostaining to determine the amount of axonal damage, in adjacent sections. Rat brain diagrams of 4 (from a total of 8) selected coronal planes, with the areas containing tau-positive oligodendrocytes indicated by black shading, 22 h after either permanent or transient MCA occlusion in the rat (Valeriani et al, 2000). This method showed that the extent of oligodendrocyte pathology was significantly less after early reperfusion compared with permanent ischemia and that this was accompanied by less neuronal and axonal damage (Valeriani et al, 2000).…”
Section: Fig 4 Quantitation Of Tau-positive Oligodendrocytes In Iscmentioning
confidence: 99%
“…4). For example, in the study of Valeriani et al (2000), the volume of tissue containing tau-positive oligodendrocytes, in animals that had experienced early reperfusion of the tissue after 2 h of intraluminal-thread MCAO, was reduced compared with that in animals subjected to permanent artery occlusion. Early tissue reperfusion significantly reduced oligodendrocyte pathology in the cerebral cortex but reduced it to a much lesser degree in subcortical areas.…”
Section: Protection Of Oligodendrocytes From Ischemia In Vivomentioning
confidence: 99%